The impact of the use of personal-protective-equipment on the minimization of effects of exposure to pesticides among farm-workers in India - Lari, Summaiya; Yamagani, Praveen; Pandiyan, Arun; Vanka, Janardhan; Naidu, Mohan; Senthil Kumar, Balakrishnan; Jee, Babban; Jonnalagadda, Padmaja R. (Frontiers in Public Health, 2023)
Although excessive use of pesticides and unsafe agricultural practices may contribute to numerous intoxications, the role of PPE (personal-protective-equipment) in the minimization of toxicological effects due to pesticide exposure has not been addressed so far. The present study aimed to assess the impact of the use of PPE on the minimization of effects of exposure to pesticides among farm-workers. A community-based follow-up study with questionnaire-based survey and field observations was undertaken among farm-workers (n=180) of Rangareddy district, Telangana, India. Biomarkers of exposure such as cholinesterase activity, inflammatory markers (TNF-a, IL-1b, IL-6, cortisol, and hs-C reactive protein), nutrients (vitamins A, E), liver function (total protein and A/G ratio, AST and ALT levels) were investigated in the laboratory by following the standard protocols. Farm-workers who had a mean farming exposure of 18 years of and who neither followed safe pesticide handling practices nor used PPE and also showed reluctance to obey good agricultural practices (GAPs). Inhibition of AChE (acetylcholine esterase) with increased inflammation was found among farm-workers as compared to their respective normal values when they have not used PPE. Linear regression statistical analysis revealed a profound effect on inhibition in the AChE activity and various inflammatory markers with the increase in the duration of pesticide exposure. Further, there was no effect of the duration of pesticide exposure on the levels of vitamins A, E, ALT, AST, total protein, and A/G ratio. Further, intervention studies carried out on the use of PPE provided (commercially available and cost-effective) for 90 days showed a significant reduction in the biomarker levels (p<0.01). This study demonstrated the importance of the use of PPE during pesticide applications and other agricultural tasks to minimize pesticide-associated adverse health effects.